Implementasi Sistem Komunikasi Nirkabel OFDM Berbasis Software Defined Radio (SDR) - Ida Anisah; Hendy Briantoro; Ahmad Zainudin; Desy Intan Permatasari (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
Nowadays, wireless communication technology is developing rapidly. However, this technology still has some weaknesses, e.g. large bandwidth requirement and multipath fading. To overcome these weaknesses, MIMO OFDM technique is needed. This paper implements MIMO OFDM 2x2 communication system in Universal Software Radio Peripheral (USRP). The performance of MIMO OFDM 2x2 is shown by the throughput value. This value is compared to the throughput value of single carrier and SISO OFDM. The modulations used are BPSK, 4-QAM, and 16-QAM. In 4-QAM modulation, the throughput value of MIMO OFDM is significantly larger than throughput value of single carrier and SISO OFDM. The throughput value of single carrier communication system is 27.71 Mbit/s, while the throughput value of the SISO OFDM communication system is 60.27 Mbit/s, and the throughput value of the MIMO OFDM 2x2 communication system is 123.03 Mbit/s.